Dangke: Pangan Lokal (Kajian Historis dan Nilai Budaya di Desa Pinang Kecamatan Cendana Kabupaten Enrekang) - Sri Fatmawati Mustamin; Mr. Jumadi; Dimas Ario Sumilih (Rayhan Intermedia, 2022)
This study aims to determine the history of local food made and known by the people in Pinang Village, Cendana District, Enrekang Regency, the traditional process of making dangke and its development, as well as the cultural value of dangke as local food. This research is a type of qualitative descriptive research. Data collection techniques were carried out using observation, interviews, and documentation. Based on the results of this study, it shows that: (1) The historical study of dangke is that the name